HUBUNGAN ANTARA PERENCANAAN STRATEGIS SI/TI DENGAN KINERJA ORGANISASI DI TINGKAT UNIVERSITAS - Herdin Herdin; M. Imam Akbar Hairi (UNIVERSITAS INDO GLOBAL MANDIRI)
Strategic planning for information systems is essential to organisational success, especially in times of increasingly rapid change.In order to reach the objective of the university in its vision and mission, it needs business strategy and IS/IT strategy. The basic concept in arranging framework IS/IT strategic planning is John Ward and Joe Peppard’s concept. The framework of IS/IT strategic planning has compiled a few methods of strategic planning. The results of the research showed that IS/IT Strategic Planning is Significant with the Performance of the organization and obtained by the study of needs of IS/IT in IGM University generating application portfolio will be implemented in the institution